2013
DOI: 10.1002/mar.20647
|View full text |Cite
|
Sign up to set email alerts
|

Shame‐Free Guilt Appeals: Testing the Emotional and Cognitive Effects of Shame and Guilt Appeals

Abstract: Although many health communication researchers use the terms “shame” and “guilt” interchangeably, arguably these constructs are distinct and have widely divergent psychological consequences. The purpose of this study was to explore distinct cognitive and emotional outcomes resulting from shame relative to guilt appeals. Specifically, this paper provides empirical evidence that negative outcomes such as anger and perceived manipulative intent are more likely to be associated with shame than guilt. Using an expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 46 publications
3
73
1
2
Order By: Relevance
“…Although recent research has expanded the view of guilt appeals in light of the related emotion of shame, arguing that the two affects likely have different impacts on the persuasion process (e.g., Boudewyns et al, 2013;Duhacheck et al, 2012), it appears the role of positive emotions, like relief or hope, within this context is still unexplored. Yet on the basis of the fear-based evidence, as well as theory of guilt arousal and resolution, the flow of emotions from guilt to relief (or guilt to hope or anger or shame) likely has important implications for the success or failure of guilt appeal messages.…”
Section: Emotional Shifts In Persuasive Messagesmentioning
confidence: 97%
See 1 more Smart Citation
“…Although recent research has expanded the view of guilt appeals in light of the related emotion of shame, arguing that the two affects likely have different impacts on the persuasion process (e.g., Boudewyns et al, 2013;Duhacheck et al, 2012), it appears the role of positive emotions, like relief or hope, within this context is still unexplored. Yet on the basis of the fear-based evidence, as well as theory of guilt arousal and resolution, the flow of emotions from guilt to relief (or guilt to hope or anger or shame) likely has important implications for the success or failure of guilt appeal messages.…”
Section: Emotional Shifts In Persuasive Messagesmentioning
confidence: 97%
“…Thus, it is possible the persuasive power of guilt may motivate productive health behavior under appropriate circumstances. However, such conditions have yet to be specified, though current efforts are attempting to address this issue (e.g., Boudewyns, Turner, & Paquin, 2013;Duhacheck, Agrawal, & Han, 2012).…”
Section: Discrete Emotions and Persuasive Influencementioning
confidence: 97%
“…One study of shame-free guilt messaging related to STD testing demonstrated that messages focusing on guilt while not also eliciting shame were more effective than shame or combined guilt/shame-focused messaging in producing positive behavior change. 35 Conversely, a tobacco control intervention reported greater recall of a shame-based social isolation messaging, 36 but problems with that study interfere with its ability to be generalized. 37 For instance, they did not measure shame or guilt in participants and the most memorable message was also the only novel message, creating a potential confound.…”
Section: Discussionmentioning
confidence: 99%
“…Shame produces various feelings, such as embarrassment, inadequacy and selfcontempt (Tangney & Dearing, 2002). Furthermore, Boudewyns, Turner, and Paquin (2013) found that shame was related to perceived devious intent and anger, whereas guilt was not.…”
Section: Introductionmentioning
confidence: 93%